2019
DOI: 10.37358/mp.20.2.5371
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis with Finite Elements of the Elasto-plastic Behaviour of the Spinal Immobilizers - in the Case of Comminutive Fractures

Abstract: In this paper it is presented a comparative theoretical study - performed by finite element analysis (FEA), of the tension state that appears at the level of the spine, as well as in the areas adjacent to it, under the following conditions: a) the existence of a comminutive fracture at the level of the vertebra T11; b) of the external immobilization of the body through a Lombax orthesis (LO) or of the internal immobilization of the column by means of a spinal fixator (SF); c) of performing some basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the evolution of finite-element analysis and numerical simulation software for heat transfer phenomena, a general trend of the extension of the research approach from case studies to numerical analysis and simulation can be observed [22][23][24]. Thus, the analysis of particular phenomena leads to the establishment of models on the basis of which the simulation of the influence of the thermal spraying process phenomena can be carried out, in order to achieve efficiency in terms of cost versus optimization time.…”
Section: Introductionmentioning
confidence: 99%
“…With the evolution of finite-element analysis and numerical simulation software for heat transfer phenomena, a general trend of the extension of the research approach from case studies to numerical analysis and simulation can be observed [22][23][24]. Thus, the analysis of particular phenomena leads to the establishment of models on the basis of which the simulation of the influence of the thermal spraying process phenomena can be carried out, in order to achieve efficiency in terms of cost versus optimization time.…”
Section: Introductionmentioning
confidence: 99%
“…Complex problems of decision have the following characteristics that lead to the difficulty of solving them, [5,6]:…”
Section: Introductionmentioning
confidence: 99%